A mycological study of dermatophytosis in a tertiary health care centre in Central Karnataka. - A Sumanta; Jagadevi; DS Shubha; KS Sudhindra; B Saipriya (Tropical Journal of Pathology and Microbiology, 2022)
Background Dermatophytic infections caused by keratinophilic fungi including genera Trichophyton, Epidermophyton, and Microsporum. The hot and humid climatic condition of central Karnataka promotes fungal infection. This study was done to determine the most predominant species of Dermatophyte causing infection in this region, which helps in treatment.Methodology The study was a cross sectional, descriptive study conducted in the department of Microbiology for a period of 6 months. All the patients who were clinically diagnosed with dermatophytosis were included in the study. Infected hair, nail or skin scrapings were taken as samples and KOH mount and fungal culture done in all these samples. Slide culture was also done to speciate. Species were correlated with treatment history.Results Out of 146 samples analysed for different dermatophyte species, 124 (84.93%) grew Trichophyton mentagrophytes, and 19 (13%) grew Trichophyton rubrum. One each of Trichophyton tonsurans, Microsporum canis and Microsporum gypseum were also isolated.Conclusion The most common isolated dermatophyte species in our study was Trichophyton mentagrophytes which is same as in many studies from India, a shift from Trichophyton rubrum to Trichophyton mentagrophytes. Since in Trichophyton mentagrophytes, many times antifungals are not sensitive, treatment should be done carefully in line with the literature on Trichophyton mentagrophytes antifungal susceptibility testing. Also, we recommend more studies with Antifungal susceptibility testing.